GWAS of Hematuria. Issue 5 (May 2022) - Gagliano Taliun, Sarah A.; Sulem, Patrick; Sveinbjornsson, Gardar; Gudbjartsson, Daniel F.; Stefansson, Kari; Paterson, Andrew D.; Barua, Moumita
Visual Abstract: Abstract : Background and objectives: Glomerular hematuria has varied causes but can have a genetic basis, including Alport syndrome and IgA nephropathy. Design, setting, participants, & measurements: We used summary statistics to identify genetic variants associated with hematuria in White British UK Biobank participants. Individuals with glomerular hematuria were enriched by excluding participants with genitourinary conditions. A strongly associated locus on chromosome 2 ( COL4A4 - COL4A3 ) was identified. The region was reimputed using the Trans-Omics for Precision Medicine Program followed by sequential rounds of regional conditional analysis, conditioning on previous genetic signals. Similarly, we applied conditional analysis to identify independent variants in the MHC region on chromosome 6 using imputed HLA haplotypes. Results: In total, 16, 866 hematuria cases and 391, 420 controls were included. Cases had higher urinary albumin-creatinine compared with controls (women: 13.01 mg/g [8.05–21.33] versus 12.12 mg/g [7.61–19.29]; P <0.001; men: 8.85 mg/g [5.66–16.19] versus 7.52 mg/g [5.04–12.39]; P <0.001) and lower eGFR (women: 88±14 versus 90±13 ml/min per 1.72 m 2 ; P <0.001; men: 87±15 versus 90±13 ml/min per 1.72 m 2 ; P <0.001), supporting enrichment of glomerular hematuria. Variants at six loci ( PDPN, COL4A4-COL4A3, HLA-B, SORL1, PLLP, and TGFB1 ) met genome-wide significance ( P <5E-8). At chromosome 2, COL4A4 p.Ser969X (rs35138315; minor allele frequency=0.00035; P <7.95E-35; odds ratio, 87.3; 95% confidence interval, 47.9 to 159.0) had the most significant association, and two variants in the locus remained associated with hematuria after conditioning for this variant: COL4A3 p.Gly695Arg (rs200287952; minor allele frequency=0.00021; P <2.16E-7; odds ratio, 45.5; 95% confidence interval, 11.8 to 168.0) and a common COL4A4 intron 25 variant (not previously reported; rs58261427; minor allele frequency=0.214; P <2.00E-9; odds ratio, 1.09; 95% confidence interval, 1.06 to 1.12). Of the HLA haplotypes, HLA-B ( *0801 ; minor allele frequency=0.14; P <4.41E-24; odds ratio, 0.84; 95% confidence interval, 0.82 to 0.88) displayed the most statistically significant association. For remaining loci, we identified three novel associations, which were replicated in the deCODE dataset for dipstick hematuria (nearest genes: PDPN, SORL1, and PLLP ). Conclusions: Our study identifies six loci associated with hematuria, including independent variants in COL4A4 - COL4A3 and HLA-B . Additionally, three novel loci are reported, including an association with an intronic variant in PDPN expressed in the podocyte. Podcast: This article contains a podcast at https://www.asn-online.org/media/podcast/CJASN/2022_04_26_CJN13711021.mp3